ICT adoption drives productivity in developed and developing countries - Halimahton Sa’diah Let; Hanny Zurina Hamzah; ZulkornainYusop; Nur Syazwani Mazlan (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study examined the impact of ICT adoption on productivity in developed and developing countries. Data was gathered among 44 developed and 45 developing countries between 2009 and 2015. As identified in previous literature, the key factors that determine productivity are capital, labour, ICT, human capital, prices, research and development (R&D). The data was analysed using the generalized method of moments (GMM). Findings show that ICT adoption drives labour productivity in developed countries, despite the high mobile broadband prices. There is also an indication that people enjoy being connected regardless of the the increase in the price of broadband, in order to enhance their productivity. However, it was observed that ICT adoption has insignificant impact on productivity in the developing countries. Lastly, developing countries were found to have larger inputs of labour and capital which increased their producitivity.